Pengembangan Media Pembelajaran Hidroponik Mini Berbasis Aquaponik pada Materi Teknologi Reproduksi pada Tumbuhan di Kelas IX MTs Negeri Gowa - Hatim, Ahmad; Hamansah, Hamansah; Arif, Wiwin Pramita (Indo-MathEdu Intellectuals Journal, 2025)
This research aims to develop a mini hydroponic learning media based on aquaponics on the topic of plant reproduction technology in class IX MTs Negeri Gowa. The type of research conducted is research and development or R&D, adapting the ADDIE model. The participants involved in this research are 34 students from class IX MTs Negeri Gowa. The tools used in this research include validation sheets, questionnaires, performance evaluation, product assessment, portfolios, and learning outcome tests, all of which have been validated. The analysis techniques applied include data analysis regarding validity, practicality, and effectiveness. The research results indicate the development of mini hydroponics using ADDIE which consists of five stages: analysis, design, development, implementation, and evaluation. The validity level of mini hydroponics received a score of 3.51, which falls into the very valid category. The practicality level of mini hydroponics reached 83% and is classified as very practical. This study shows that all 34 students scored above the minimum competency standard (KKM), with a percentage of 100%, thus mini hydroponics is declared an effective tool.